KEPENTINGAN AMERIKA SERIKAT DALAM PROGRAM DEBT FOR NATURE SWAPS (DNS) DI INDONESIA TAHUN 2009-2013 - ", Nurrinawati; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The goal of this research is analyzing the interest of United States of America on DNS program in Indonesia. The governments of Indonesia and United States of America have a deal about the agreement in decreasing debt of Indonesia governments partly as donation for natural conservation. This agreement will be implemented on Debt for Nature Swaps (DNS) program.The method of this research is qualitative research by using explorative method with library research technique used some references that is literatures, articles of scientific journal, and relevant resources. By using theory of national interest concept that is stated by Jack c Plano and Roy Olton, there is interest of creditor country (United States of America) in supporting debtor country (Indonesia) in decreasing their debt through Debt for Nature Swap (DNS) program.The result of this research is making of united states interest on Debt for Nature Swap (DNS) program in Indonesia as the building of economy and politic on natural conservation in Indonesia through TFCA (The Tropical Forest Conservation Action) design that is TFCA1 and TFCA2.Keywords: United States of America, Indonesia, Debt for Nature Swap, Interest.